Age-related and Gender Characteristics of the Content of Subjective Experiences of Mental States in Children with Developmental Disorders - Лира В. Артищева (Rossijskij psihologičeskij žurnal., 2020)
Introduction. This study addresses age-related and gender characteristics of subjective experiences of mental states in children with developmental disorders. Methods. The authors examined subjective experiences of mental states such as joy, anger, and calmness. Children were asked to retrospectively and prospectively describe their mental states. The method of content analysis of texts was employed to identify semantic units and calculate the frequency of their occurrence. Results. Subjective experiences of mental states in children with developmental disorders depend on their gender and age. Subjective experiences of certain mental states may have similar content in boys and girls. Subjective experiences of mental states are more pronounced in younger boys with infantile cerebral palsy than in younger girls and in adolescent boys. Experiences of mental states are significantly enriched in adolescent girls with infantile cerebral palsy. Adolescents’ subjective experiences depend on gender and mental state. Subjective experiences of the state of joy are significantly more pronounced in younger boys with severe speech impairments than in adolescent boys. Boys’ experiences of calmness have a similar content. Younger girls’ experiences of calmness are much more intense than that of the boys of the same age. Projecting into the future, subjective experiences of mental states are transformed, losing some substantial components. Discussion. The study of subjective experiences of mental states in children with developmental disorders expands the format of available research in the field of psychology of mental states. The present study appears to be the first on characteristics of the experience of mental states in children of different nosological groups. The results of this study do not contradict the available data on mental states in school-age children provided earlier by A. O. Prokhorov.